2020
DOI: 10.5343/bms.2019.0050
|View full text |Cite
|
Sign up to set email alerts
|

A novel low-cost, high-precision sea temperature sensor for coral reef monitoring

Abstract: The role of elevated sea temperatures in coral bleaching has been well documented. Many of the sea temperature records utilized for purposes of widespread, multi-species bleaching predictions in recent publications have been acquired through satellite remote sensing. Satellites estimate sea temperatures at only a narrow range of depths near the surface of the ocean and may therefore not adequately represent the true temperatures endured by the world's coral ecosystems. To better characterize sea temperature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…When calibrated properly, a platinum resistance sensor can achieve accuracy of less than a 0.001 °C [ 69 ]. In addition, compared with other temperature sensors, platinum resistive sensors are smaller which means a faster response time [ 70 ]. Thermistors are also commonly used for temperature measurements.…”
Section: Temperature Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…When calibrated properly, a platinum resistance sensor can achieve accuracy of less than a 0.001 °C [ 69 ]. In addition, compared with other temperature sensors, platinum resistive sensors are smaller which means a faster response time [ 70 ]. Thermistors are also commonly used for temperature measurements.…”
Section: Temperature Sensorsmentioning
confidence: 99%
“…The average error of the sensor is less than 2.9%. A high precision fiber optic Fabry-Perot pressure sensor with pressure sensitivity of 257.79 nm/MPa is introduced by Yanan Zhang [ 70 ]. This pressure sensor is based on an AB epoxy adhesive film.…”
Section: Depth Sensorsmentioning
confidence: 99%
“…The sensitivity experiments for the temperature measurements involv cooling tests, and included separate systems for testing the water temp ; low-speed crystal oscillator 2 ; high-speed crystal oscillator 3 ; data storage chip 4 ; low-power linear voltage regulator chip 5 ; type-c data communication interface 6 ; rechargeable storage battery 7 ; TS-V1 temperature probe 8 ; ritanium alloy shell cap 9 ; titanium alloy shell bottle body Figure 2a ①). Meanwhile, a high-speed clock crystal (depicted in Figure 2a ③) supplies timing signals to the integrated internal counter.…”
Section: Experimental Design Of Measurement Parameters and Deployment...mentioning
confidence: 99%
“…In addition, satellites only measure the near-surface layer of the water body and may not reliably measure the potential impacts of the water temperature on benthic ecosystems. The combination of remote sensing with in situ methods can improve the quality of water temperature monitoring activities [7,8]. Previous studies have shown that water temperature records based on available in situ measurements are effective for many purposes provided there is sufficient instrument spacing and precision [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although remote sensing offers broad-scale monitoring, it cannot distinguish individual coral colonies (Candela et al, 2021). In addition, expensive operational costs limit its widespread use (Hendee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%